2020
DOI: 10.1128/mra.01350-19
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences, Derived by Next-Generation Sequencing, of JC Polyomavirus Strains Isolated from Vietnamese Renal Transplant Recipients

Abstract: JC polyomavirus (JCPyV) may cause clinical syndromes such as progressive multifocal leukoencephalopathy in immunocompromised patients. Here, we report seven complete genome sequences of JCPyV genotype 7A, generated directly from urine samples from Vietnamese renal transplant recipients by using rolling-circle amplification and next-generation sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…This result was similar to other studies that reported JCV subtype 7A was found in Asian populations 9,19 . To our knowledge, there were only a few reports that identified JCV subtype 7A and 7B1 in Vietnamese patients 20,21 but JCV subtype 7C1 was for the first time observed in this study. It was also proposed that the identification of JCV genotypes can be used for tracing the migration and evolution of JCV 22 .…”
Section: Discussionsupporting
confidence: 92%
“…This result was similar to other studies that reported JCV subtype 7A was found in Asian populations 9,19 . To our knowledge, there were only a few reports that identified JCV subtype 7A and 7B1 in Vietnamese patients 20,21 but JCV subtype 7C1 was for the first time observed in this study. It was also proposed that the identification of JCV genotypes can be used for tracing the migration and evolution of JCV 22 .…”
Section: Discussionsupporting
confidence: 92%